Enabling a gasification and carbon capture economy in India: An integrated techno-economic analysis. (1st March 2020) - Mukherjee, Atanu; Maity, Arunava; Chatterjee, Saikat
Abstract: India emits over 2.4 gigatons of CO2 [1, 2] today and will continue to see the biggest increase in fossil fuel CO2 emissions. This is partly due to rapid economic growth, industrialization, and efforts to bring electricity to rural communities. Apart from restructuring the power sector through progressive adoption of high efficiency low emission (HELE) power plants with potential carbon capture, pre-combustion carbon capture along with syngas based industrial production and petrochemical feedstock substitution can lay the foundations for an economically viable, less carbon emission intense industrial future for India. One of the biggest opportunities for carbon dioxide abatement through clean coal technology lies in using India's abundant low rank coal reserves through coal gasification and carbon capture to enable and expand a carbon neutral industrial economy, which today emits close to 25% [1–3] of the total greenhouse gases (GHG). A practical and holistic macro and micro-level techno-economic analysis is an essential pre-requisite for enabling a clean coal-based industrial economy in a cost-sensitive developing country like India. Through this study, the key sectors that can be enabled using coal gasification and carbon capture are identified and the viable techno-economic options, macro-economic and trade impact, policy support options and a carbon capture finance model for India are analyzed.